New paradigms of USP53 disease: normal GGT cholestasis, BRIC, cholangiopathy, and responsiveness to rifampicin - Alhebbi, Hamoud; Peer-Zada, Abdul Ali; Al‐Hussaini, Abdulrahman A.; Algubaisi, Sara; Albassami, Awad; AlMasri, Nasser; Alrusayni, Yasir; Alruzug, Ibrahim M.; Alharby, Essa; Samman, Manar A.; Ayoub, Syed Zubair; Maddirevula, Sateesh; et al. (Journal of human genetics, 2021)
Biallelic variants in the USP53 gene have recently been reported to segregate with normal gamma glutamyltransferase (GGT) cholestasis. Using whole-exome sequencing (WES), we detected two USP53 homozygous variants (c.951delT; p. Phe317fs and c.1744C>T; p. Arg582*) in five additional cases, including an unpublished cousin of a previously described family with intractable itching and normal GGT cholestasis. Three patients, a child and two adults, presented with recurrent episodes of normal GGT cholestasis, consistent with a diagnosis of benign recurrent intrahepatic cholestasis (BRIC). Cholangiopathic changes, possibly autoimmune in origin, were recognized in some patients. Additional phenotypic details in one patient included an enlarged left kidney, and speech/developmental delay. Notably, two patients exhibited a complete response to rifampicin, and one responded to ursodeoxycholic acid (UDCA). Two adult patients were suspected to have autoimmune liver disease and treated with steroids. This report describes new cases of USP53 disease presenting with normal GGT cholestasis or BRIC in three children and two adults. We also describe the novel finding of a dramatic response to rifampicin. The association of cholangiopathy with normal GGT cholestasis provides a diagnostic challenge and remains poorly understood.